PROCESS MAPPING AND MODELING WITH BPMN: BEST PRACTICES AND IMPLEMENTATION CHALLENGES - Garcia Medeiro, Juliana (Humanas em Perspectiva, 2025)
The Business Process Model and Notation (BPMN) has established itself as the de facto standard for business process modeling globally. This article presents a Systematic Literature Review (SLR) aiming to identify and analyze the best practices and implementation challenges of BPMN, focusing on academic production from the last five years (2020-2025). The research covered high-impact scientific databases, resulting in the identification of emerging trends and persistent problems in the Business Process Management (BPM) discipline. The results reveal that while BPMN is fundamental for Business-IT alignment and process automation, its implementation faces significant obstacles, such as the lack of objectivity in modeling, the difficulty in dealing with process granularity, and the need to incorporate domain knowledge and common sense into analysis tools. Best practices are intrinsically linked to the Critical Success Factors (CSFs) of BPM, with Top Management Support, Business-IT Alignment, and the adoption of a robust Implementation Methodology standing out. This study contributes to the consolidation of knowledge in the field, providing an updated and robust overview for researchers and professionals seeking to optimize the application of BPMN in their organizational contexts.